Tissue culture applied to carnivorous species - Caldeira, Mariana Maestracci Macedo; Jesus, José Victor Maurício de; Magalhães, Hemelyn Soares; Carvalho, Maria Antônia Santos de; Andrade, Monielly Soares; Nunes, Claudineia Ferreira (Scientia Agraria Paranaensis, 2021)
The purpose of the review is to comment on available data on the application of plant tissue culture to carnivorous plants. Thus, the review encompassed publications from 1979 to 2017 along in vitro germination studies and micropropagation techniques, such as somatic embryogenesis and organogenesis, which emphasized the responses of plant materials to the stimuli offered during in vitro culture. Tissue culture in carnivorous plants is presented as a tool to promote the increase of the population of these plants either for scientific and commercial purposes or for the conservation and reintroduction in their natural habitat, in order to ensure a sustainable exploitation of this nutritional pattern of plants. In general terms, the studies carried out were limited to the following aspects: cultivation technique, explant source, exogenously applied substances and culture medium. The review also revealed the absence of defined protocols for in vitro multiplication of large-scale carnivorous plants.